Development of Spanish Version of Home-Based Video Module of Balance Exercises for Peripheral Vestibular Disordered Patients - Zuraida Zainun; Sarmiento E S; Mohd Normani Zakaria; Dinsuhaimi Sidek (International Journal of Brain Sciences, 2024)
Any disturbances affecting one or more of the balance organs lead to imbalance difficulties and as a consequence, the quality of life of the affected individuals can be seriously affected, especially if the episodes end with injuries or even fatal accidents. Bal Ex is the first home-based video guided workout that was created by Zainun and her colleagues in 2009. Ten languages are currently supported by Bal Ex, including Cantonese, Malay, English, Mandarin, Hokkien, Tamil, Persian, Arabic, Nigerian, and Spanish (Appendix 1). With permission, several changes were made to this module from its original version, CCCE . Bal Ex has twenty exercises that are broken down into three levels: postural movement, placement, and head and neck movement. This module offers a lot of advantages and is simple to use because it provides step-by-step instructions along with audio and visual hints. Second, because it is provided at home, patients can receive therapy without regularly visiting the hospital. In addition to being more flexible, this is also useful for patients with disabilities. Long-term cost effectiveness is also achieved indirectly. Above all, Bal Ex can enhance a patient's quality of life and balance symptoms in less than three months. According to our experiences, the majority of chronic peripheral cases had a positive outcome, feeling an improvement two to three months after starting an activity program. Here, we offer an illustration of a case that was handled well: Due to the complexity of vestibular illnesses, vestibular rehabilitation is one option for treating individuals with vestibular disorders and assisting in their recovery. These physical therapy have been shown to be quite effective. Indeed, patients and physicians gain from having a home-based therapy that works. Targeting various components of the balancing system, the video-guided instructions are provided in an easy-to-follow and methodical manner. Subsequent research ought to compare this video module's efficacy in situations of central vestibular problem and Parkinson's disease. It will be interesting to observe if this physical activity helps with other disease causes like stroke.
Keywords: Balance exercises; Home-based therapy; Quality of life; Vestibular rehabilitation; Video- guided workout